Thomas and Friends Fun and Bumps (London Egmont, 2016)
Thomas the Tank Engine is here to help engage children and inspire them to read with confidence. This book includes two stories about Thomas' friends. In one we meet Fergus, the little traction engine and in the other, Rusty, who is always working hard. With colourful pictures, short sentences and simple, phonetic-based vocabulary, children will love learning to read with Thomas. Level 1 Reading Ladder titles are perfect for new readers who are beginning to read simple stories with help. Thomas has been teaching children lessons about life and friendship for over 70 years. He ranks alongside other beloved character such as Paddington Bear, Winnie-the-Pooh and Peter Rabbit as an essential part of our literary heritage
English stories
Level 1
2
Keywords: English stories